Urban toll: Rethinking acceptability through accessibility - Yves Crozet; Aurélie Mercier (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper examines the optimal level of public transport pricing in metropolitan areas, using Stockholm and Paris as case studies. It shows that overall welfare improves if public transport prices are increased during peak hours to balance demand and fund additional services in the peak. This report considers the sources of welfare improvements and compares the effect of such pricing policy on cities with and without road pricing.
Keywords: 330